El género Cancer L. en el Pacífico mexicano (Crustacea: Decapoda: Brachyura) - Carvacho, Alberto (1989)
Eight species of Cancer occur in Mexico, all of them exclusively on the Pacific Coast: C. anthonyi, C. antennarius, C. productus, C. gracilis, C. jordani, C. branneri, C. amphioetus, C. johngarthi, the first four of which are commercially exploited. A revision of synonymies, time-space distribution patterns, morphology, size and bioecological notes for each species is presented along with the results of a one year sampling survey in 31 stations of Bahia de Todos Santos ( 31°40'N; 116°40'W). A key to all species is provided.